Concrete scientific methodology of the problem of forming the future musical art teacher’s ethnocultural competence - Larysa Solyar (Pedagogical Discourse, 2018)
The article is devoted to the concrete scientific methodology of the problem of forming the future musical art teacher’s ethnocultural competence. The purpose of the article, which consists in revealing theoretical principles of the concrete scientific methodology of investigating the problem of forming the future musical art teacher’s ethnocultural competence, is determined. The tasks described are the following – to study the problem of the concrete scientific methodology of forming the future musical art teacher’s ethnocultural competence, which provides for conducting theoretical analysis of the pedagogical foreign and domestic experience; to carry out an essential characteristic of the basic concepts in the context of the problem under investigation. Acmeological approach, which determines the peculiarities of forming ethnocultural competence of the future musical art teacher as a professional capable of achieving the top professional mastery, is revealed. The approach involves focusing on obtaining excellence and effectiveness in the creative training of the future musical art teachers. Professiographic approach provides for the future musical art teachers’ mastery of the active-role (professional) characteristics; defines the teacher’s professional activity as a system of interrelated elements characterizing his professional orientation, knowing the science fundamentals, possessing ethnocultural competence. Ethnocultural approach reflects the revival of family folk traditions, customs, the respect for family and domestic culture, which contributes to forming the future teachers’ deep feelings; it is based on the principle of ethnoculturalism, the dialogue of cultures, cultural creativity, tolerance, and the relationship of education with the ethnocultural environment, based on the key ethnocultural traditions in education aiming to form ethnocultural personality. Competence approach is defined as the basic one in researching ethnocultural competence and in training future musical art teacher. The approach provides for the high degree of formation of the future musical art teacher’s ethnocultural competence in the process of the successful pedagogical activity, which ensures activation of the mechanisms of the general and professional self-development and each student’s motivation.